Multidimensional challenges in Brazil's decision-making process of vaccines adoption: The case of childhood pneumococcal conjugate vaccines - Ana Marli Christovam Sartori; Patrícia Coelho de Soárez; Hillegonda Maria Dutilh Novaes; Thayssa Veiga da Fonseca Victer; Ana Catarina de Melo Araujo; Greice Madeleine Ikeda do Carmo; Marcelo Yoshito Wada; Eder Gatti Fernandes (Journal of Infection and Public Health, 2025)
The objective of this paper was to examine the process of adopting new vaccines in a middle-income country. Methods: We used an intrinsic explanatory case study to analyze the recent decision-making process of switching 10-valent Pneumococcal Conjugate Vaccine (PCV10) to PCV13 in the Brazilian childhood immunization schedule. We analyzed Conitec (Comissão Nacional de Incorporação de Tecnologias no Sistema Único de Saúde) official documents. Results: In November 2022, the Conitec plenary recommended, at first, switching from PCV10 to PCV13, considering PCV13 non-inferiority and similar safety profile to PCV10, the price proposed by Wyeth/Pfizer, below the currently practiced, and the scenario of possible resource savings observed in an economic analysis conducted by Wyeth/Pfizer. In a second meeting, in April 2023, Conitec final decision was not to introduce PCV13 at that moment, based on additional scientific, administrative and technical data presented by the National Immunization Program, mainly epidemiological data showing no recent increase of pneumococcal disease (PD), the need to increase vaccination coverage to better control PD and to implement a sentinel surveillance of vaccine-preventable bacterial diseases with nationwide representation to better evaluate PD burden and serotypes replacement, and the country technological development and self-sufficiency in vaccine production. Conclusions: Our case showed the decision-making process of adopting new vaccines is country-specific and involve many levels of political prioritization and complex technical aspects, and depends on the presence of strong public health institutions.